Dendrimers as tunable vectors of drug delivery systems and biomedical and ocular applications - Kalomiraki M (Dove Medical Press, 2015)
Marina Kalomiraki,1 Kyriaki Thermos,2 Nikos A Chaniotakis1 1Laboratory of Analytical Chemistry, Department of Chemistry, 2Department of Pharmacology, School of Medicine, University of Crete Voutes, Heraklion, Greece Abstract: Dendrimers are large polymeric structures with nanosize dimensions (1–10 nm) and unique physicochemical properties. The major advantage of dendrimers compared with linear polymers is their spherical-shaped structure. During synthesis, the size and shape of the dendrimer can be customized and controlled, so the finished macromolecule will have a specific “architecture” and terminal groups. These characteristics will determine its suitability for drug delivery, diagnostic imaging, and as a genetic material carrier. This review will focus initially on the unique properties of dendrimers and their use in biomedical applications, as antibacterial, antitumor, and diagnostic agents. Subsequently, emphasis will be given to their use in drug delivery for ocular diseases. Keywords: nanoparticles, ocular diseases, encapsulation, macromolecule, diagnostic agent